Educação para as mídias no ensino médio: perspectivas para o século XXI - Gaidargi, Alessandra Maria Martins (2013)
The present research investigates the involvement of young High School students in education projects for the media education, in public and private schools in the city of São Paulo, and the relation of the development of these projects with the motivation of young people attending school, acting part in reducing truancy at this level of education and upgrading the value of High School for the students. Considering the proximity bigger every day among youth and the media, whether analogical or digital, the inclusion of technology in a dialogic High School may represent a link between the world of young people and the school they attend. The study takes on the theoretical references of integration of the fields of education and communication, highlighting the theories of Paulo Freire and Jürgen Habermas, and statistics about the current situation of High School, and also brings the results of field research conducted with a thousand of young people that lives in São Paulo city about their involvement in projects of media education. The survey results indicate that media education projects in the city of São Paulo are numerous in High Schools, but have varying degrees of autonomy of the students and different forms of organization for educational institutions, sometimes moving away from the concept of media education as a proposal to develop critical thinking and citizenship of the students. The statements made by the interviewees indicated that media education can be an issue generating of new perspectives for High School in the XXI century.